Kursus Bimbingan Belajar GenBi (Generasi Bijak) di SD Gajah Mada Medan - Panjaitan, Simon Maruli; Manurung, Anggun Rezeky Marito; Purba, Koleta A.A; Simaremare, Rodia Mestina; Situmorang, Lidia Erika; Siregar, Koko Mai (Indonesia Berdaya, 2022)
The Tridharma of Higher Education includes community service programs. The application, practice, and application of knowledge and technology that is utilized as a tool to enhance a nation's education is the purpose of PKM. Essentially, a teacher is the most important person in the realm of education since the instructor is the one who determines whether or not a lesson is successful. Learning will also be hindered if a teacher has a strong social spirit; this is necessary for efficient communication between students and instructors, which must be two-way. This community service allows students to put what they've learned in class into practice, apply what they've learned, and experience what they've learned.